INTELLECTUAL PROPERTY RIGHTS IN THE DIGITAL ERA (Challenges and Opportunities for Creative Industry Players in Indonesia) - Arya Saputra, Dimas; Lestari Putri, Ayu; Indah Permata, Rani (Jurnal Multidisipliner Bharasa, 2024)
The digital age has brought a major transformation to the creative industries, enabling wider distribution and access to creative works. However, this also poses new challenges in the protection of intellectual property rights (IPR) for creative industry players in Indonesia. This article aims to examine the challenges and opportunities faced by creative industry players in protecting IPR in the digital era. This research uses a qualitative approach by collecting data through literature studies and interviews with several relevant stakeholders, including creative industry players, IPR observers, and authorities. The results show that although the digital age offers significant market expansion opportunities for creative industry players, challenges such as copyright and brand infringement are becoming increasingly complex. The study also identifies weaknesses in the current legal framework that affect the effectiveness of IPR protection and offers several recommendations to address those challenges, including regulatory improvements, increased awareness of IPR, and strengthened interagency cooperation. This article contributes to an understanding of the dynamics of IPR in the digital era in Indonesia and provides insight for policymakers, legal practitioners, and creative industry players in optimizing the potential of the creative industry while protecting the rights of creators and innovators.